Lingkungan Kerja dan Motivasi Pengaruhnya Terhadap Kinerja Karyawan PT. Putriana Jaya Utama - Hermin Andi Magga; A Bintang Balele (Pusat Riset dan Inovasi Nasional, 2021)
The purpose of this study is to identity and analyze the impact of motivation and good working environment on employee. The responden of study are employees of PT. Putriana Jaya Utama with a sample of 40 people.Methods of collecting observation data, questionnaires and documentation, and using data analysis methods, namely descriptive analysis of percentages, research instruments, classical assumption tests and hypothesis testing using SPSS 21 software for Windows. The calculation results are optaining the impacts of motivation and employee working performance is t count of 3,623 to 0,001 sig. The impact of working environment on employee working performance t count of 3,038 to 0,004 sig. The impact of motivation and working environment on employee working performance F count of 42,819 to 0,000 sig. As such motivation and the working environment have positive and significant impact on employee working performance. And the calculation of Coefficient of determination (R2) both motivation and working environment have an impacts of the working performance of 69,8%.